Si and Zn co-doped InGaN-GaN white light-emitting diodes. - Chang, S.J.
InGaN-GaN double heterostructure (DH) and multiquantum-well (MQW) light-emitting diodes (LEDs) with Si and Zn co-doped active well layers were prepared by metalorganic chemical vapor deposition (MOCVD). It was found that we could observe a broad long-wavelength donor-acceptor (D-A) pair-related emission at 500∼560 nm. White light can thus be achieved by the combination of such a long-wavelength D-A pair emission with the InGaN band-edge-related blue emission. By increasing the DMZn mole flow rate to 360 nmole/min, we could achieve a Si and Zn co-doped In0.3Ga0.7N-GaN MQW LED with color temperature of 4100 K, color rendering index of 70, and color coordinates x=0.383, y=0.405. It was also found that the 20-mA forward voltage and the breakdown voltage of such Si and Zn co-doped In0.3Ga0.7N-GaN MQW LEDs were both smaller than those of the conventional phosphor-converted white LEDs.
Keywords: 500 to 560 nm; DH LED; InGaN-GaN white light emitting diode; InGaN-GaN:Si.; Zn; MQW LED; Si/Zn co-doping.; Band-edge blue emission; Breakdown voltage; Color coordinates; Color rendering index; Color temperature; Donor-acceptor pair emission; Forward voltage; Metalorganic chemical vapor deposition